Pengembangan Instrumen Soal IPA SD Berbasis STEM Materi Pola Sebab Akibat Siswa Fase A - Sukamto Sukamto; Siti Patonah; Lia Fitriani (STKIP Andi Matappa Pangkep, 2023)
In a learning activity, it is necessary to have an initial assessment as a measuring tool in describing the initial conditions of students. The reality in the field is that teachers have not made STEM-based initial instruments to determine students' initial conditions, so it is necessary to develop initial instruments so that teachers can find out students' initial conditions so that the material provided is in accordance with students' needs. The purpose of this study was to develop initial instruments to determine the readiness of students in the learning activities of phase A students in science learning material on STEM-based causal patterns. The research method used is the R&D research method consisting of: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results of the study can be concluded that the STEM-based STEM-based primary science instrument for phase A students is 0.73-0.84 (moderate to high) for the Aiken index.